2022
DOI: 10.1101/2022.07.13.499916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Chromatin Data Supports a Role For CD14+ Monocytes/Macrophages in Mediating Genetic Risk for Juvenile Idiopathic Arthritis

Abstract: IntroductionGenome wide association studies (GWAS) have identified multiple regions that confer genetic risk for the polyarticular/oligoarticular forms of juvenile idiopathic arthritis (JIA). However, genome-wide scans do not identify the cells impacted by genetic polymorphisms on the risk haplotypes or the genes impacted by those variants. We have shown that genetic variants driving JIA risk are likely to affect both innate and adaptive immune functions. We provide additional evidence that JIA risk variants i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A role of IL-6 in oJIA has been implied decades ago (42). In addition, a recent study investigating chromatin data in monocytes in JIA patients found that IL-6 binding was one of the top enriched processes (9). Peeters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role of IL-6 in oJIA has been implied decades ago (42). In addition, a recent study investigating chromatin data in monocytes in JIA patients found that IL-6 binding was one of the top enriched processes (9). Peeters.…”
Section: Discussionmentioning
confidence: 99%
“…T-and B-cells are thought to play a role, given the genetic relationship to MHC class II alleles and the presence of ANAs (4)(5)(6). Though, the contribution of members from the innate immune system, such as monocytes, is becoming increasingly recognized (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%